EXTENDING KANNAN AND CHATTERJEA THEOREMS IN 2-BANACH SPACES BY USING SEQUENTIALLY CONVERGENT MAPPING - Malčeski, Aleksa; Ibrahimi, Alit; Malčeski, Risto (Matematichki Bilten, 2016)
S. Gähler ([8]), defined a 2-normed and A. White ([1]) a 2-banach space Further, the contractive mapping in 2-normed space in [4] is defined by in P. K. Hatikrishnan, K. T. Ravindran. In [2] and [10], there are given generalizations of Kannan ([5]) and Chatterjea ([9]) fixed points theorems in 2-Banach spaces. In this paper by using sequentially convergent mappings, the results given in [2] and [10] will be generalized in 2-Banach spaces. They might also be considered as generalizations of the results given in [11].